PERBANDINGAN KEKERASAN RESIN AKRILIK TIPE HEAT CURED PADA PERENDAMAN LARUTAN DESINFEKTAN ALKALIN PEROKSIDA DENGAN EKSTRAK SELEDRI (APIUM GRAVEOLENS L.) 75%) - Dewi Puspitasari; Debby Saputera; Rizky Noor Anisyah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: One of the acrylic resins properties is the water absorption that affect on the hardness changes of the acry/ic resins. This /aboratory experiments studied disinfectant Alkaline peroxide and celery (Apium graveolens L.) extract 75% effect on the hardness changes of acry/ic denture base resins materia/. Purpose: This study aims to determine the effect of immersion denture cleanser alkalin peroxide and celery (Apium graveolens L.) extract 75% of the hardness acrylic resin.Methods: The study a pure experimental study with posttest-only with control group design. The study was conducted by immersing heat cured acrylic samples of 30 mm of diameter and 5 mm of thickness in alkaline peroxide, ce/ery (Apium graveo/ens L.) extract 75% and aquades for 5 and 15 days. An Vickers Microhardness Testing Machine using the Vickers indentation technique with (50 gr load for 10s) were used for the hardness changes observationResults: The statistical test used One-way ANOVA and Bonferroni with 0.05 significance degree /eve/. The average va/ue of acry/ic hardness in a/ka/ine peroxide and celery extract 5 days 15.01 VHN and 15.37 VHN, 15 days 13.77 VHN and 14.07 VHN.Conclusion: The resu/t showed no significant difference hardness of acry/ic resins denture base plate after immersion in Alkaline peroxide and celery (Apium graveolens L.) extract 75% for 5 and 15 days.